Optimization and Clinical Validation of Colorimetric Reverse Transcription Loop-Mediated Isothermal Amplification, a Fast, Highly Sensitive and Specific COVID-19 Molecular Diagnostic Tool That Is Robust to Detect SARS-CoV-2 Variants of Concern - Alves, Pedro A.; de Oliveira, Ellen G.; Franco-Luiz, Ana Paula M.; Almeida, Letícia T.; Gonçalves, Amanda B.; Borges, Iara A.; Rocha, Flávia de S.; Rocha, Raissa P.; Bezerra, Matheus F.; Miranda, Pâmella; Capanema, Flávio D.; Martins, Henrique R.; et al. (Frontiers in Microbiology, 2021)
The COVID-19 pandemics unfolded due to the widespread SARS-CoV-2 transmission reinforced the urgent need for affordable molecular diagnostic alternative methods for massive testing screening. We present the clinical validation of a pH-dependent colorimetric RT-LAMP (reverse transcription loop-mediated isothermal amplification) for SARS-CoV-2 detection. The method revealed a limit of detection of 19.3 ± 2.7 viral genomic copies/μL when using RNA extracted samples obtained from nasopharyngeal swabs collected in guanidine-containing viral transport medium. Typical RT-LAMP reactions were performed at 65 ºC for 30 min. When compared to RT-qPCR, up to Ct value 32, RT-LAMP presented 98 % (95-99.5 % 95 % CI) sensitivity and 100% (94.5-100 %) specificity for SARS-CoV-2 RNA detection targeting E and N genes. No cross-reactivity was detected when testing other non-SARS-CoV virus, confirming high specificity. The test is compatible with primary RNA extraction free samples. We also demonstrated that colorimetric RT-LAMP can detect SARS-CoV-2 variants of concern (VOC) and variants of interest (VOI), such as variants occurring in Brazil named Gamma (P.1), Zeta (P.2), Delta (B.1.617.2), B.1.1.374 and B.1.1.371. The method meets point-of-care requirements and can be deployed in the field for high-throughput COVID-19 testing campaigns, especially in countries where COVID-19 testing efforts are far from ideal to tackle the pandemics. Although RT-qPCR is considered the gold standard for SARS-CoV-2 RNA detection, it requires expensive equipments, infrastructure and highly trained personnel. In contrast, RT-LAMP emerges as an affordable, inexpensive and simple alternative for SARS-CoV-2 molecular detection that can be applied to massive COVID-19 testing campaigns and save lives